Integrating LC-MS and HS-GC-MS for the metabolite characterization of the Chinese medicinal plant Platostoma palustre under different processing methods - Tang, Danfeng; Quan, Changqian; Huang, Suhua; Wei, Fan (Frontiers in Nutrition, 2023)
Platostoma palustre (or Mesona chinensis Benth) is an important medicinal and edible plant in China and Southeast Asian countries. To study the effects of different processing methods on the quality, nutrition, and flavor of P. palustre, we adopted the LC-MS and HS-GC-MS to compare the influences of tedding (S), sweating (M), and drying (H) on the metabolites and volatile substances of P. palustre. Biochemical determinations revealed that the M treatment could promote the accumulation of the contents of total sugar, soluble sugar, and total pectin compared to the H and S treatments, but decrease the total flavonoid contents. LC-MS and HS-GC-MS uncovered 98 differential metabolites and 27 differential volatile substances among the three treatments, respectively. Overall, the M treatment facilitated the stabilization and improvement of the quality of polysaccharide and volatile substances, while the H treatment could promote the level of amino acids in P. palustre. The current study provided a theoretical reference for establishing standardized processing methods and sustaining the quality stability of P. palustre in the future.